Equity and effectiveness in East African primary schools - Zuze, Tia Linda (School of Economics, 2014)
Researchers and policy makers agree that studying the relationship between school qualityand academic achievement will benefit public investment in education. An important turningpoint in educational delivery in Africa came during the 1990 World Conference on Educationfor All where renewed commitments to quality basic education were made. Against thisbackground, interest in how African education systems are progressing has increased. Thisthesis contributes to this understanding in three important ways. The first and broadestobjective is to assess the role of comparative studies in setting educational standards. Thesecond relates to how schools within three East African education systems can contribute tothe academic success of students whatever their background. The third is to investigate whichschools most effectively ensure a meaningful educational experience for children who faceeconomic and social hardships. Data are sourced from the second wave of a cross-nationalsurvey of schools in Southern and Eastern Africa. Hierarchical Linear Modelling is used toanalyse data on schools and students in Kenya, Tanzania and Uganda.The results demonstrate that, although valuable for establishing general patterns of effects,comparative studies should be followed by further investigation of the salient issues at workwithin individual countries. Contrary to earlier studies in developing countries, anunambiguous positive relationship between socioeconomic status and student performancewas evident across this region. Compositional, structural and organisational characteristics ofEast African primary schools were found to be related to academic achievement. Academicallysupportive relationships between students and household members benefited studentperformance in Kenya and Tanzania. In line with the school effectiveness theory, resourceavailability proved to be consistently related to educational quality and its equitable distributionin Uganda. An important finding relating to gender was that characteristics of schools thatimproved quality did so more effectively for boys than for girls and therefore increased themale academic advantage. The implication is that the climate for learning in East Africanprimary schools is better suited to educating boys.The study recommends that future surveys pay closer attention to how student attitudes tolearning are shaped so that schools can play a more effective role in motivating students. Totease out exactly how the educational environment influences learning, it is also recommendedthat more longitudinal studies be pursued by the educational research community. That thepace of educational reform is often painfully slow makes the use of longitudinal data to track itscourse all the more necessary.